A combined kinetic analysis for thermal characteristics and reaction mechanism based on non-isothermal experiments: The case of poly(vinyl alcohol) pyrolysis. (1st March 2023) - Zhao, Jun; Chen, Zhili; Bian, Huiting
Highlights: One combined kinetic analysis method was introduced. Non-isothermal TGA experiments for PVA were conducted at four heating rates. Kinetic triplets were obtained by both model free and model fitting approaches. Optimal mechanisms were reconstructed based on F3/2 and F2 models respective for two decomposition stages. Abstract: This work aims to implement one efficient combined kinetic approach for determining thermal kinetic triplets and elucidating reaction mechanism for poly(vinyl alcohol). Thermogravimetric pyrolysis profiles were acquired in inert nitrogen atmosphere with 5, 10, 15, and 20 K/min heating rates, and its thermal decomposition behavior was characterized in details. With respect to two main stages identified in whole pyrolysis process, their activation energies varying with conversion extents were computed by applying several model free methods, including FWO, KAS, FR, and advanced isoconversion approaches. Subsequently, the linear CR and non-linear masterplots model fitting methods were to severely figure out the appropriate reaction mechanism functions. Of particular interest is observed that F3/2 and F2 mechanism models were separately deemed to be appropriate for two stages, but they failed in giving good overlapping details with experimental data. Furthermore, a combined kinetic analysis was carefully conducted to obtain kinetics triplets, which includes model independent analysis and thoroughly considers kinetic compensation effect. Thereby, accurate reaction models were separately optimized and reconstructed for two distinct pyrolysis steps by the imported accommodation functions. This work finally provides a precise methodology to gain insight into thermal behavior and decomposition mechanism of poly(vinyl alcohol), and improve the prediction accuracy of kinetics.